PERLINDUNGAN HUKUM TERHADAP KEASLIAN CERITA RAKYAT - Asih K.Tus, Desyanti Suka (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2014)
Requirement of originality is determined by Article 1 paragraph (3) Act Number 19 of 2002 on Copyright can be easily applied to new creations, but when it comes to creations such as traditional folktale takes more search to determine their originality. Folktale began to transferred into another form that is more interesting, but reduce the element of originality to the story so the younger generation may not know the real form of the folktale. Based on that background, this study discussed problem about originality concept on copyright in a work, Act Number 19 of 2002 on Copyright and the Berne Convention and the legal protection on originality of folktale. This study is a normative legal research, using the statute approach and the conceptual approach. The outcome of this study show that the provisions of the originality of an inventions as set forth in Article 1 paragraph (3) of Act Number 19 of 2002 on Copyright defined creativity as the basis for determining the originality of a work. Protection for the originality of folktale can be done with the passage and implementation of documentation Article 15 and Article 35 of Act Number 19 of 2002 on Copyright.
Keywords: Legal protection; Originality of Folktale